Distorções e contradições no cinturão citrícola alagoano: aspectos da produção e comercialização agrícola entre 2008 e 2011 - Silva Júnior, Alonso Barros da (2014)
The present work presents as main idea a study of distortions and contradictions citrícola alagoano belt: aspects of agricultural production and marketing between 2008 and 2011. Study the process of marketing of an agricultural product in a city or region is of fundamental importance, since it enables generation of knowledge of how the market works and behaves. When speaking, therefore, in no way makes cultures ignore varieties such as the orange tree, which is the main variety of citrus produced and marketed in the State of Alagoas, and only with great economic and social importance, thanks to its historic roots. The data collected for the dissertation shows that there is a strong concentration of establishments producing orange in the region known as vale do mundaú, besides a high concentration, that represents more than 90% of the State's production, destined to the CEASA/AL. Despite this strong rooting and all soil and climate conditions presented, it does not translate into development for the region , the human development index (HDI) with the municipalities in the region as being one of the worst in the State. Fact that only comes to confirm the hypothesis that in spite of all potential and of the factors that elevate the region as polo Orange producer in Alagoas, it is not reflected in economic and social development, by the fact that most of the income generated by the production of Orange stay in the hands of middlemen because of the distortions caused by these intermediary agents during the process of commercialization. The work also verified through analysis model of transmission of prices and marketing margins, which the producers anything interfere in pricing in the marketing channel of the product to get to the wholesale market, that is, there is some difficulty in passing on the farm to wholesale price that does not influence your pricing In addition there is a strong producer price distortion to the wholesaler, which in most of the four years studied, holds a relative negative margin, featuring so prejudice, thanks to greater volatility in their prices in relation to prices charged by the manufacturer, which is characterized by a greater inherent stability, market conditions.